ANALISIS PEMASARAN DAN SIKAP KONSUMEN TERHADAP PEMBELIAN IKAN PATIN SALAI UMKM BINAAN INKUBATOR AGRIBISNIS UNIVERSITAS RIAU - Juliati Samosir; Ahmad Rifai; Fajar Restuhadi (Fakultas Pertanian, Universitas Riau, 2014)
The fisheries sector (which is made up of capture fisheries and aquaculture) is one of the most important household economics in Kabupaten Kampar, both of economic and social standpoints.The smoked fisheries industry further supports almost 12 % of households (directly and indirectly), and contributes to the livelihood, employment, and household food security, especially for communities live along the Kampar’s Delta. Currently, several fisheries small-holder’s enterprises were assisted by The Agribusiness Incubator, University of Riau, in terms of processing, packaging, and marketing techniques. This research was aimed to study marketing and behavioural analysis of smoked catfish produced by the enterprises.The respondents mostly purchase the smoked catfish directly to the Wholesale/Dealer/Collector. The respondent’s purchasing decision is mostly affected by the following product attributes: packaging, point of sale location, and service offered by the seller. Plotting the product’s attributes in the Cartessian diagram shows that the first quadrant is filled by the following attributes: product’s aroma, brand, price, and smoked fish color. The second quadrant is described by hygienic properties, weight per pack, taste, and saltiness property. Meanwhile, for the third quadrant is positioned by the products’s nutrition information and labeling; as well as for the fourth quadrant is the location of sales, service sales, and forms of packaging. Based on the analysis of Fishbein’s Multiatributes, the respondent’s attitude is considered as fairly-good on the multiattributes categorical approach.